Prioritization of the Use of Individual Assets Based on the Ta’awun Economic Concept - Luqmanulhakim, Luqmanulhakim (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
Wealth is God's gift to mankind. In Islam, humans are given the right to own property, but in some parts there are parts that are the rights of other people. The exercise of these rights is regulated in the zakat mechanism, and as a vehicle for increasing charity, infaq and alms are also available. Islam wants the realization of an economic system where people have an awareness of each other that comes from enlightenment in terms of helping each other (ta'awun), mutually guaranteeing each other so that overall there is a socio-economic building that strengthens each other. With the ta'awun economic framework, every Muslim individual needs to have a pattern of using assets that maximizes the usefulness of these assets for the benefit of the people. Every asset must be productive and especially in the form of money it must flow. After expenditures in the nature of daruriyah and hajiyat have been paid, a Muslim's assets need to be used to drive the economy with the concept of ta'awun economics. We tried to formulate economic activity in two measurement parameters, readiness for material profit and loss, by producing four quadrants as follows: tijarah activity, tijarah and tabarru’, high risk tabarru’, and low risk tabarru’.